Locating the Manhattan housing market: GIS evidence for 1880-1910 - Rowena Gray; Rocco Bowman (Queen's University Centre for Economic History (QUCEH), 2020)
There is a dearth of systematic information about the historical New York City housing market. We present anew sample containing rental price and characteristic data for almost 10,000 Manhattanunits which was collected from historical newspapers for the period 1880 to 1910. These units were geolocated to the historical map of Manhattan Island to explore theirgeographic coverage, using Geographic Information System (GIS) software. We use this new sample to plot the evolution ofthe locationand quality of available Manhattanhousing units.This complements existing research on the growth of New York City and the evolution of the ethnic composition of neighborhoods across Census years, as we show information at annual frequency during this time of high growth for the city.
Keywords: N31; N91; R31; 330; historical GIS; New York City; housing markets; neighborhood change